A Bibliometric Study on Articles Published in PubMed-indexed Prosthodontic Journals in the Year 2016 - Basnet, Bishal Babu; Gyawali, R.; Allhaj, M.N. (Journal of Nepalese Prosthodontic Society, 2018)
Introduction: Publication trends of Prosthodontic literature in the PubMed-indexed journals in the year 2016 was studied to assess the number of authors, country affiliation of principal author, international collaboration in authorship, type of studies, major field of study. The bibliometric study helps to determine the scientific growth and development. Aims and objectives: The aim of this study was to explore the prosthodontics literature in PubMed-indexed journals in the year 2016. Materials and methods: All the published articles excluding the book review, letter to editor, panel discussion etc were assessed and the data regarding the number of authors, affiliation of principal author, international collaboration in authorship, type of studies, number of references were entered into Microsoft Excel and analyzed for demographic findings. Results: 645 articles satisfied the inclusion criteria. Principal authors from Asian countries contributed for major bulk of the studies (51%). Major emphasis of study is attracted to dental materials, CADCAM, zirconia, cements (categorized under “other” in this study). The in-vitro studies were more prevalent in the year 2016 (>35%). Though international collaboration has been found in many articles, single authorship has decreased (4.81%). Conclusion: The collaboration amongst authors is increased but international collaboration is still less and the newer topics of interest are being studied rather than conventional prosthetic sciences.